Airway management in neonates with Pierre Robin sequence - Gözü, Aydin; Genç, Bülent; Palabiyik, Murat; Unal, Murat; Yildirim, Güven; Kavuncuoğlu, Sultan; Ozsoy, Zafer (The Turkish Journal of Pediatrics, 2010)
Neonates with Pierre Robin sequence (PRs) suffer from varying degrees of airway obstruction and feeding difficulties, the courses of which differ from patient to patient, due to mandibular deficiency. We aimed to evaluate the course and prognosis of upper airway obstruction in 20 newborns with PRs. Among 15 isolated and 5 syndromic cases, 7 patients fell into Group I, 5 into Group II and 8 into Group III, respectively, according to the clinical classification system proposed by Caouette-Laberge. The 12 patients in Groups I and II were treated with positioning and gavage feeding, whereas the 6 patients in Group III underwent bilateral mandibular distraction. Decannulation or avoidance of tracheostomy was achieved in all of them. A patient who had a significant comorbidity was managed with tracheostomy and one patient expired due to pulmonary problems. When conservative measures fail, mandibular distraction osteogenesis should be considered to obviate tracheostomy in newborns with micrognathia.